HUBUNGAN STATUS SOSIAL EKONOMI ORANG TUA DENGAN TINGKAT KEBUTUHAN PERAWATAN ORTODONTI SISWA SMPN 1 MARABAHAN - Novarina Haryanti; Diana Wibowo; Ika Kusuma Wardani (Dentin, 2020)
ABSTRACTBackground: Malocclusion can be treated with orthodontic treatment. The essentials in orthodontic treatment are the factor of socioeconomic status (education, work, and income). The parents with high socioeconomic are capable to give the awareness to conducting visits to the dentist for giving dental and oral health knowledge and treatment, compared with the parents with low socioeconomic. Purpose: Aims to find the correlation between the parent’s socioeconomic status with the orthodontic treatment need level students in SMPN 1 Marabahan. Methods: Observational analytic research with a cross-sectional study. The sample was taken by Simple Random Sampling. The research sample were 46 respondents. Data were obtained by questionnaire and Handicapping Malocclusion Assessment Record. Results: The parent’s education that is SMA/SMK/MA/Equal and Diploma/Bachelor has the most frequency, which is 21 people. The Permanent Employee has the most frequency, which is 28 people. The highest frequency is at the middle economy level, which is 32 people. The orthodontic treatment need level in score 20 or higher has the most frequency, which is 28 students. The result of the Spearman analysis test obtained that significances are 0,014, 0,036, and 0,042 (p-value <0,05). Conclusion: There is a correlation between the parent’s socioeconomic status with the orthodontic treatment need level students in SMPN 1 Marabahan Keywords: the socioeconomic status, malocclusion, orthodontic treatment need level ABSTRAKLatar Belakang: Maloklusi dapat dirawat dengan perawatan ortodonti. Hal yang perlu dipertimbangkan dalam perawatan ortodonti adalah faktor status sosial ekonomi, yaitu pendidikan, pekerjaan, dan pendapatan. Orang tua dengan status sosial ekonomi tinggi mampu memberikan kesadaran untuk melakukan kunjungan ke dokter gigi dalam hal pemberian pengetahuan anak tentang kesehatan gigi dan mulut dan perawatan gigi dibandingkan orang tua dengan sosial ekonomi rendah. Tujuan: Mengetahui hubungan status sosial ekonomi orang tua dengan tingkat kebutuhan perawatan ortodonti siswa SMPN 1 Marabahan. Metode: Penelitian analitik observasional dengan pendekatan cross sectional. Pengambilan sampel dilakukan dengan Simple Random Sampling. Sampel penelitian berjumlah 46 responden. Data diperoleh dengan kuesioner dan Handicapping Malocclusion Assessment Record. Hasil: Tingkat pendidikan orang tua pada jenjang pendidikan SMA/SMK/MA/Sederajat dan Diploma/Sarjana memiliki frekuensi terbanyak, yaitu 21 orang. Tingkat pekerjaan Pegawai Tetap memiliki frekuensi terbanyak, yaitu 28 orang. Frekuensi terbanyak pada tingkat pendapatan ekonomi menengah, yaitu 32 orang. Tingkat kebutuhan perawatan ortodonti pada skor 20 ke atas memiliki frekuensi terbanyak, yaitu 28 siswa. Hasil uji analisis Spearman diperoleh signifikansi secara berurutan, yaitu 0,014, 0,036, dan 0,042 (p-value <0,05). Kesimpulan: Terdapat hubungan antara status sosial ekonomi orang tua dengan tingkat kebutuhan perawatan ortodonti siswa SMPN 1 Marabahan. Kata kunci: status sosial ekonomi, maloklusi, tingkat kebutuhan perawatan ortodonti